2004
DOI: 10.2337/diabetes.53.2.315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moderate Exercise Training on Peripheral Glucose Effectiveness, Insulin Sensitivity, and Endogenous Glucose Production in Healthy Humans Estimated by a Two-Compartment-Labeled Minimal Model

Abstract: , analyzed using the two-compartment minimal model, were significantly elevated 16 h after the last training session. The elevated S g 2 * remained higher despite the cessation of exercise training for 1 week (1.00 ؎ 0.03 ؋ 10 ؊2 dl ⅐ kg ؊1 ⅐ min ؊1 ). EGP was suppressed within 20 min after glucose bolus, and the suppression of EGP was followed by their overshoot. The time course of EGP during the intravenous glucose tolerance test remained similar after the training period. In conclusion, moderate exercise tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 39 publications
2
30
0
1
Order By: Relevance
“…Finally, although hyperglycaemic clamp-measured S I agrees well with hyperinsulinaemic-euglycaemic clamp-measured insulin sensitivity [44], glucose effectiveness is included in the hyperglycaemic clamp-measured S I [27]. In this context, Nishida et al showed that endurance training increases glucose effectiveness, which is sustained for 1 week after training cessation [45]. Thus, we cannot rule out that the increased S I seen in the IWT group was dependent on increased glucose effectiveness.…”
Section: Discussionmentioning
confidence: 73%
“…Finally, although hyperglycaemic clamp-measured S I agrees well with hyperinsulinaemic-euglycaemic clamp-measured insulin sensitivity [44], glucose effectiveness is included in the hyperglycaemic clamp-measured S I [27]. In this context, Nishida et al showed that endurance training increases glucose effectiveness, which is sustained for 1 week after training cessation [45]. Thus, we cannot rule out that the increased S I seen in the IWT group was dependent on increased glucose effectiveness.…”
Section: Discussionmentioning
confidence: 73%
“…The groups had similar body weight presurgery and preinterventions. Both groups also reported similar improve glucose effectiveness (S G ) in healthy individuals following a 12-week exercise program (17). Exercise increases oxidative enzyme activity in skeletal muscle and induces related biochemical and morphological changes that would seem to confer a metabolic basis for improved S I (11,18).…”
Section: Resultsmentioning
confidence: 80%
“…Impairments in these insulin action and glucose metabolism indices are recognised as prediabetic phenotypes involving pathogenic development and pathogenetic processes of type 2 diabetes. Exercise training improves peripheral S I and S G in healthy human subjects [1], and significant improvements in S I , AIR g , DI and S G in response to 20 weeks of endurance exercise training have been observed and reported in the HERITAGE Family Study [2]. Recent investigations in HERITAGE provide further evidence that physiological training responses vary appreciably from person to person, and these individual differences are influenced by genetic factors [3].…”
Section: Introductionmentioning
confidence: 95%